Magnetosheath and solar wind turbulence processes features identification - Prokhorenkov, A.S.; Kozak, L.V.; Lui, A.T.Y. (Advances in Astronomy and Space Physics, 2015)
A different kind of analysis should be applied to a turbulent process, than that applied to a nondisturbed medium. In this work we present the result of extended self-similarity analysis (ESS) by comparing between different turbulent models: Kolmogorov K41 model, She-Leveque (isotropic log-Poisson model) of order 3; Iroshnikov-Kraichnan model and Politano-Pouquet model of order 4. Two regimes were observed for large and small times
ales: the Gaussian distribution was used for small times ales for magnetic field fluctuation probability distribution function (PDF), and the Lèvy distribution was used for large-scale timescale non-Gaussian distributions. The intersection of two asymptotes corresponds to approximately 1 s, which agrees with the ion-cyclotron period.